Науково-методичне забезпечення оцінювання конкурентних переваг підприємств на засадах маркетингу у ризикованих умовах господарювання - Соколова, Л. В.; Дюжев, В. Г.; Аль-Фахор Ескндер Суліаман Салти (ПУ «Причорноморський науково-дослідний інститут економіки та інновацій», 2023)
У статті досліджено, що у сучасних умовах агресивного та турбулентного зовнішнього середовища потребує подальших досліджень питання осучаснення науково-методичних підходів до процесу оцінювання конкурентних переваг підприємств промислового сектору. Визначено значущість та актуальність розгляду у повоєнний період питань науково-методологічної спрямованості щодо підвищення рівня конкурентоспроможності вітчизняних промислових підприємств на основі їх конкурентних переваг на засадах маркетингу. Запропоновано провадити формування сукупності показників конкурентних переваг підприємства у форматі комплексу маркетингу «5Р’s». Доведено доцільність застосування імітаційної моделі оцінювання конкурентних переваг на основі індексного інтегрального показника в ризикованих умовах господарювання. The article focuses on the insufficient attention of scientists to the issue of ensuring the competitive advantages of enterprises of the industrial sector and their assessment on the basis of marketing. It is noted that in conditions of turbulence in the external environment, the assessment of the competitive advantages of an industrial enterprise usually precedes the stage of assessing the level of its competitiveness, and subsequently the formation of its corporate strategy. The importance, relevance and necessity of further research in the direction of improving scientific and methodical approaches to the rocess of evaluating the competitive advantages of industrial enterprises in the modern conditions of an aggressive external environment have been determined. A scheme for the implementation of the process of ensuring the development of scientific and methodological support for the evaluation of the competitive advantages of the enterprise on the basis of marketing has been drawn up. This scheme contains ten main meaningful blocks (stages). The content of each stage is considered. The implementation of the proposed scientific and methodological approach required the selection of the main groups of competitive advantages of the investigated enterprise and the reference enterprise. For this, it was proposed to use the format of the "5P's" marketing complex, which consists of product, price, place, promotion and financial position. The components of each group of this marketing complex, which are actually related to the competitiveness of the company's products, are considered. A coordinated group of independent experts was formed. They evaluated the local indicators (elements) of each group of the complex according to the selected point scale and the specific weight of each group. Next, the averaged composite score was calculated for each local indicator and each component of the "5P's" marketing complex. A simulation model has been synthesized for calculating the index integral indicator of the assessment of competitive advantages in the conditions of risky business. The analysis of the obtained calculation data allows to investigate the dependence of the influence of inflation on the numerical value of the index of the integral indicator of the assessment of the competitive advantages of the investigated enterprise in the conditions of business risk.
Scientific-Methodical Ensuring The Assessment of Competitive Advantages of Enterprises on The Basis of Marketing in Risky Economic Conditions
Keywords: конкурентна перевага; комплекс маркетингу «5Р’s»; competitive advantage; marketing mix "5P's"